Fatigue Resistance of the Advanta V12/iCast and Viabahn Balloon-Expandable Stent-Graft as Bridging Stents in Experimental Fenestrated Endografting. (June 2021) - Torsello, Giovanni; Müller, Marcus; Litterscheid, Sarah; Berekoven, Bärbel; Austermann, Martin; Torsello, Giovanni-Federico
Purpose: Bridging stents undergo millions of cycles during respiratory movements of the kidneys throughout the patient's life. Thus, understanding the response of fabric and endoskeleton of the stent to cyclic loading over the time is crucial. In this study, we compare the fatigue resistance of the Viabahn Balloon-Expandable stent-graft (VBX) with the widely used Advanta V12/iCast under prolonged stress induction. Materials and Methods: A polyester test sheet with 10 fenestrations was used simulating a fenestrated endograft. Five 6×59 mm VBX stent-grafts and five 6×58 mm Advanta stent-grafts were implanted into 6×6 mm fenestrations. The stents were flared with a 10×20 mm PTA (percutaneous transluminal angioplasty) catheter and connected with a fatigue stress machine. All stent-grafts were evaluated by microscopy and radiography at baseline and after regular intervals until 50, 000, 000 cycles were applied, simulating a life span of approximately 75 months. Freedom from fracture (FF), freedom from initial polytertafluoroethylene (PTFE) changes (FIC), and from PTFE breakpoint (FBP, all-layer defect) were calculated. Results: Digital radiographic images did not show any stent fracture in both groups after 50, 000, 000 cycles. The VBX stent-graft was free from any all-layer defects at the conclusion of 50, 000, 00 cycles resulting in a significant higher FBP compared with Advanta V12 (50, 000, 000 vs 33, 400, 000; p<0.01). All-layer defects were observed only in the Advanta group. Two of 5 Advanta stents showed early penetration of the nitinol ring causing a defect of PTFE. Regarding FIC, there was no significant difference between the stents (3, 400, 000 in VBX vs 3, 200, 000 in Advanta). Conclusions: In fatigue tests simulating respiration movements, VBX and Advanta V12 performed equally well in terms of fracture resistance and freedom from initial PTFE changes. VBX maintained freedom from PTFE breakpoint throughout the full 50, 000, 000 cycles. All-layers defects were detected only in Advanta and were mainly caused by penetration of the nitinol ring through the PTFE.